The Trait Theory of Leadership and The Eight-Fold Noble Path as Buddhist Leadership Paradigm: A Stark Scrutiny - Bastola, Dipak (Research Nepal Journal of Development Studies, 2020)
This paper titled, The Trait Theory of Leadership and The Eight-Fold Noble Path as Buddhist Leadership Paradigm: A Stark Scrutiny, strives to explore an affinity between the trait theory and the eight-fold noble path, to scrutinize the theoretical and practical implication of the integrated approach of both from the Nepalese perspective, and to expedite potential paradigm shift to enhance the leadership competencies of the 21st century. It is a conceptual paper. The secondary data has been profoundly analyzed to accumulate required facts, details, and information through comprehensive literature reviews. In conclusion, there is an obvious and precise affinity between both conceptions to propose an integrated paradigm transmutation for the enhancement of leadership competencies of the 21st century. From the Nepalese perspective, the empirical implication and application of the integrated leadership approach with the amalgamation of both i.e. the trait theory and the eight-fold noble path are seen inevitable as well as undeniable.